Competitive Adsorption: Reducing the Poisoning Effect of Adsorbed Hydroxyl on Ru Single‐Atom Site with SnO2 for Efficient Hydrogen Evolution. (24th August 2022) - Zhang, Jiachen; Chen, Guangbo; Liu, Qicheng; Fan, Chuang; Sun, Dongmei; Tang, Yawen; Sun, Hanjun; Feng, Xinliang
Abstract: Ruthenium (Ru) has been theoretically considered a viable alkaline hydrogen evolution reaction electrocatalyst due to its fast water dissociation kinetics. However, its strong affinity to the adsorbed hydroxyl (OHad ) blocks the active sites, resulting in unsatisfactory performance during the practical HER process. Here, we first reported a competitive adsorption strategy for the construction of SnO2 nanoparticles doped with Ru single‐atoms supported on carbon (Ru SAs‐SnO2 /C) via atomic galvanic replacement. SnO2 was introduced to regulate the strong interaction between Ru and OHad by the competitive adsorption of OHad between Ru and SnO2, which alleviated the poisoning of Ru sites. As a consequence, the Ru SAs‐SnO2 /C exhibited a low overpotential at 10 mA cm −2 (10 mV) and a low Tafel slope of 25 mV dec −1 . This approach provides a new avenue to modulate the adsorption strength of active sites and intermediates, which paves the way for the development of highly active electrocatalysts. Abstract : A novel Ru SAs‐SnO2 /C elecotrocatalyst with low OHad poisoning effect to Ru sites was demonstrated by the competition adsorption strategy. It exhibited excellent HER activity owing to the fast OHad transfer process (OHad +e − ⇋OH −, the key step of Vomer step), which alleviated the poisoning of OHad on Ru sites and facilitate regeneration of Ru active sites.